Teaching Racial Reckoning: The CRT Panic as a Challenge and an Answer - Schneider, Matthew Jerome (Radical Teacher, 2023)
Regular media coverage and social media discussion about Black Lives Matter, prison abolition, racialized police violence, and voter disenfranchisement mean that students arrive to our classes already primed to discuss and reckon with questions of racial justice and racial oppression and privilege. At the same time, we have also observed a groundswell of white Americans mobilizing in defense of white supremacy. Although this reckoning has been long in the making, recent successes of a violent and increasingly mainstream political movement have created new challenges for instructors teaching about racism. In this teaching note, I reflect on an experience with students who completed a “knowledge assessment survey” and how this was leveraged into a productive conversation about Critical Race Theory (CRT). More broadly, I suggest that discussion of politicized topics poses some challenges, but also presents opportunities for demonstrating the importance of critical race perspectives and prompts students to reflect on how their understandings of race are derived from their social worlds.